Decolonization of Communication Products and Education in Africa: A Revisit to Cultural Imperialism - Ukam, John I.; Ngwu, Ukam I. (ALSYSTECH Journal of Education Technology, 2025)
This paper examines the ongoing impact of cultural imperialism on Africa’s intellectual and communication landscape, particularly in the realms of media and education. It highlights the issue of Africa's dependence on foreign media products, which often undermine indigenous cultural values and knowledge systems. While some scholars argue that cultural imperialism is obsolete, reframing it as cultural synchronization or pluralism, the paper challenges this view by questioning the viability of globalization dominated by Western ideologies and technology. The study explores historical and contemporary examples of cultural imperialism, assessing the dominance of Western media and its effects on local communication practices. It also proposes strategies for decolonizing media and education to foster cultural diversity, autonomy, and better representation of African perspectives.